Educational Politics and Policy Change in Neoliberal Times: An Argumentative Discourse Analysis - Yoon, Ee-Seul; Winton, Sue; El Masri, Amira (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2024)
With the rise of neoliberal reforms and efforts to privatize education, there is a growing need to examine how actors and groups from the public and private sectors influence educational policy change together. In this article, we advance a critical approach to understanding the changing discursive space of educational politics by following discourses through an expansive policy network that goes beyond its traditional boundaries. Specifically, we draw on argumentative discourse analysis (ADA), which allows for the analysis of how and why various actors and groups come together to assign certain meanings to educational phenomena or problems, leading to policy responses or changes. Rooted in Foucault’s notions of discourse and power, ADA offers a unique approach to discourse analysis that can illuminate policy change through discourse coalitions. Three case studies from educational policy scholarship are discussed to illustrate the value and utility of ADA in future critical education policy studies.